A study of Seasonal Variation in the Incidence of Acinitobacter Baumanii Isolated from Infected Burn Wounds and their Antibiotic Susceptibility Patterns in a Tertiary Care Burns Hospital - Zubeda Irshad, Munir Hussain, Tehmina Jalil, Rabbia Mahboob (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Acinetobacter baumannii is a major pathogen in burn wound infections due to its resilience in hospital environments and high levels of multidrug resistance. Seasonal variation in its incidence has been reported globally, yet data from specialized burn care settings in Pakistan remain limited. Objective: To investigate seasonal variation in the incidence of Acinetobacter baumannii isolated from infected burn wounds and to evaluate its antibiotic susceptibility pattern in a tertiary care burns hospital. Methods: This retrospective cross-sectional study was conducted at the Burns and Plastic Surgery Center in Hayatabad, Peshawar, over a two-year period December 2020 to November 2022. All culture-positive A. baumannii isolates from burn wound infections were included. Data were grouped by meteorological season, and antibiotic susceptibility was assessed using the Kirby-Bauer disk diffusion method. Statistical analysis was performed using SPSS v25. Results: Out of 3884 bacterial isolates obtained from infected burn wounds, 474 (12.21%) were identified as A. baumannii. The incidence remained relatively stable across seasons, with no statistically significant seasonal variation (p = 0.74). Highest susceptibility was observed to colistin (74.1%) and tigecycline (62.5%), while high resistance was noted to cefepime (80.5%), ciprofloxacin (70.4%), and amikacin (57.7%). More than half of the affected patients had hospital stays exceeding 20 days. Conclusion: The study found no significant seasonal pattern in the incidence of A. baumannii in burn wound infections. The organism’s high resistance to most antibiotics, except colistin and tigecycline, underscores the urgency for stringent antibiotic stewardship, routine sensitivity testing, and continuous infection control practices throughout the year. Keywords: Acinetobacter baumannii, burn wound infection, incidence, seasonal variation, antibiotic resistance, multidrug resistance, colistin, tigecycline, Peshawar, ICU